How do you solve -9(-3t + 8) = -13t + 48?

3 Answers
Apr 9, 2018

t = 3

Explanation:

http://slideplayer.com/slide/9130823/http://slideplayer.com/slide/9130823/

-9(-3t + 8) = -13t + 48

"Order of Operations - "color(purple)(BEDMAS)

-9 * -3t - 9 * 8 = -13t + 48, " (Removing bracket)"

27t - 72 = -13t + 48, " (Multiplication, as also "color(brown)((-) * (-) = +)

27t + 13t = 48 + 72, "(Bringing like terms together)"

-40t = 120

t = cancel(120)^color(red)(3) / cancel40 = 3

Apr 9, 2018

First expand the brackets.

Explanation:

This gives you:

27t - 72 = -13t + 48

Then you move the unknowns to one side and the integers to the other:

27t + 13t = 48 + 72

Then simplify.

40t = 120

t = 3

Apr 9, 2018

t=3

Explanation:

So here we multiply the number before the bracket with all the numbers in the bracket, let me explain.
-9(-3t+8)=-13t+48
27t-72=-13t+48
40t - 72=48
40t=120
(40t)/40 = 120/40
t=3